Female teachers clothing styles determinants of learning attitudes of students in state colleges and universities in Luzon - Viray, Firma Caccam
This study aimed to determine and assess the teachers' clothing values and clothing styles and their influence on students' learning attitudes. Specifically, it sought to find out the types of teachers' clothing styles that contribute to negative or positive learning attitudes of students; determine the teachers' clothing values; determine teachers' attitudes in clothing selection; determine the relationship between teachers' demographic characteristics such as age, civil status, educational attainment and monthly salary and teachers' clothing values. It also sought to determine the relationship between the students' demographic characteristics of age, sex, socio-economic status and attitudes towards teachers' clothing styles; compare the clothing values between UP and non-UP teachers; compare the UP and non-UP students in their attitudes towards teachers' clothing styles; and assess if teachers' clothing styles contribute to the learning attitudes of students. One hundred forty four teachers and 746 students participated in this study. Survey questionnaires were used for data gathering. Cochran-Mantel-Haenszel test for association was utilized to test differences in teachers' clothing values, students attitudes and their demographic variables. Factor Analysis with Varimax and Harris-Kaiser Rotation was used to identify the teachers' values, and Tukey's Studentized Range (HSD) test for variables was used to test the degree of differences between each teachers' clothing style for particular attitudes of students. Findings revealed that teachers' clothing values were associated with their selection, preference, and types of clothing styles they wear in school. Results also indicated that teachers' values were associated with the teachers' demographic variables such as age, civil status, educational attainment and monthly salary. Also students' learning attitudes were associated with teachers' clothing styles and students' demographic variables such as sex, age and parents' monthly salaries. Significant differences were observed in the clothing values between UP and non-UP teachers. The same results were observed when the attitudes of students towards teachers' clothing styles were compared between UP and non-UP students. The clothing styles preferred by both students and female teachers which they perceived as appropriate and could elicit respect, credibility and discipline were the school uniform/blouse with blazer and skirt, and the blouse and trouser. The students suggested and considered the following as suitable for male teachers' attires: polo shirt and trouser, polo barong and trouser, and polo shirt and maong pants. Majority of the students seemingly disapproved the wearing of t-shirts and short pants by teachers in the classroom. Students believed that these attires were not suitable in the classroom and would tend to lower their credibility as teachers, and the respect and discipline from students. Understanding and closer evaluation of the role of clothing to positive learning attitudes of students, the selection and wearing of suitable clothing styles, and the recognition of the expectations from students and peers were suggested to teachers in order to maintain the respect and dignity of the teaching profession. It was recommended that the manner and procedure of hiring teachers must include the evaluation of the appropriateness of the clothing style they wore in school. The implementation and prescription of a suitable "dress code" for teachers in the academic institution were recommended for administrators. It was also recommended that the present guidelines on the prescribed "dress code" of the civil service be reviewed to adapt to the present need of today's teachers. Guidelines must provide assistance that facilitate innovativeness and creativeness among the teachers. It must also recognize the constraints and needs of teachers i.e. clothing allowance to ensure sustainability of these guidelines. Further researches may be conducted to determine the implications, associations and role of teachers' clothing as it influence students' attitudes in and outside the classroom.